Bringing back the Manchester Argus Coenonympha tullia ssp. davus (Fabricius, 1777): Quantifying the habitat resource requirements to inform the successful reintroduction of a specialist peatland butterfly. Issue 2 (29th May 2022) - Osborne, Andrew; Longden, Mike; Bourke, David; Coulthard, Emma
Abstract: The period 2021–2030 has been designated the UN decade of ecosystem restoration. A landscape‐scale peatland restoration project is being undertaken on Chat Moss, Greater Manchester, UK, with conservation translocations an important component of this work. The Manchester Argus Coenonympha tullia ssp. davus, a specialist butterfly of lowland raised bogs in the northwest of England, UK is under threat due to severe habitat loss and degradation. A species reintroduction was planned for spring 2020. This study aimed to quantify the resource thresholds for C. tullia, in order to assess potential risks for the project. Thirteen peatland habitat patches with either recent historic or current C. tullia populations were surveyed for biotic and abiotic factors based on previous qualitative research on the species' requirements. Percentage cover of two habitat resources was found to be the strongest predictor in models of C. tullia presence: cross‐leaved heath Erica tetralix and hair's‐tail cotton‐sedge Eriophorum vaginatum . Critical inflection points on logistic regression curves were used to make quantitative estimates of the minimum requirement of each resource for population survival and the near‐optimum abundance of each resource. The results of this study improve our understanding of C. tullia 's ecology and the restoration of peatlands for its reintroduction. Additionally, the method has wider utility for the quantitative assessment of habitat readiness before attempting species reintroductions. Abstract : Predictors of C. tullia presence were identified and quantitative estimates of important resource thresholds calculated using segmented regression of the logistic curves. Breakpoint represents the 'near‐optimal' resource level for each habitat resource, which has utility for quantitative assessment of habitat readiness prior to species reintroduction attempts.